Raymond Μ. Duch & Randolph T. Stevenson, The economic vote: How political and economic institutions condition election results - Καφέ, Αναστασία (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
No abstract